A PRACTICAL CONSIDERATION OF THE LEAD TIME DEMAND - Park, Changkyu (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
Due to the importance of lead time demand in the design of inventory management systems, researchers and practitioners have paid continuous attention to it and a few analytic models using the compound distribution approach have been reported However, since the nature of compound distributions arises a heavy analytic burden, the analytic models have been developed by non-recognition of the compound nature of some components to reduce the analytic task. Through the theoretic examination of the analytic model approach, this paper clarifies the assumptions implicitly made by the analytic models and provides some precautions in using the analytic models. An illustrative example is also presented.